EPISTIMOLOGI PENDIDIKAN ISLAM - Qifari, Abudzar Al (Jurnal Pendidikan Kreatif, 2021)
Islamic education is based on the Qur'an and Sunnah which is designed by considering the concept of science, Islamization of science and the character of science in an Islamic perspective that relies on spiritual strength that has a harmonious relationship between reason and revelation, interdependence of reason with intuition. and related to spiritual values. Episemology of Islamic education like this, becomes the foundation of hope in building a better life for Muslims with a more established and stable Islamic civilization. Epistemology of Islamic education like this emphasizes the totality of experience and reality (empiricism) and recommends many ways to study nature (rationalism), so that knowledge obtained from revelation and reason, from observation and intuition, from tradition and theoretical speculation really prints generations. balance between intellectual, skill, and spiritual as well as morality.